Evaluation of the Implementation of Work-Based Learning in the Automotive Engineering Specialisation Programme at Mandiri Private Vocational School - Muhammad Maulana Syahputra; Wakhinuddin Wakhinuddin; Hasan Maksum; Ambiyar Ambiyar (MASI Mandiri Edukasi, 2026)
Field Work Practice (FWP) is essential in vocational education for connecting school-based learning with workplace experience, yet comprehensive evaluations of FWP in Automotive Engineering remain limited. This study evaluated FWP implementation in the Automotive Engineering Program at SMK Swasta Mandiri using the CIPPO (Context, Input, Process, Product, and Outcome) model. A mixed-methods sequential explanatory design was employed. The quantitative phase involved 155 Grade XII students who had completed FWP, while the qualitative phase involved 10 informants comprising one principal, one FWP Working Group head, and eight supervising teachers. Data were collected through questionnaires, interviews, observations, and documentation, and analyzed using descriptive statistics and the Miles, Huberman, and Saldaña model. Overall FWP implementation reached 82.01%, indicating a good to very good category. Context scored 85.60% (very good), input 80.66% (good), process 79.08% (good), product 80.77% (good), and outcome 83.93% (very good). Qualitative findings indicated that variations in preparation, work activities, and industry operating conditions resulted in unequal learning experiences among students. FWP was implemented well overall but requires greater standardization of learning experiences and monitoring. The findings support CIPPO as a comprehensive evaluation framework and provide practical guidance for strengthening school–industry orientation, monitoring, competency assessment, FWP site evaluation, and graduate tracer studies.